Implementation of an Emergency Department Boarding Time Monitoring Dashboard to Reduce Patient Retention - Rejeki, Sri; Perawati, Perawati (An Idea Nursing Journal, 2025)
Background: rolonged waiting times in hospital emergency departments (EDs) are widely recognized as a major barrier to timely inpatient care and patient satisfaction. Efficient transition processes from the ED to inpatient units can reduce crowding and improve care outcomes. Methods: This study employed a descriptive survey design in Hospital X, Riau Islands, with a sample of 200 participants including ED nurses, administrative staff, and inpatient unit personnel. Data were collected using structured questionnaires and analyzed descriptively to assess the perceived impact of implementing a boarding time monitoring dashboard in the ED. Results: Prior to dashboard implementation, the proportion of patients transferred to inpatient wards within the target time (<120 minutes) was 53%. Post-implementation, compliance rose to 83.39%. Participants reported improved interdisciplinary communication, decision-making, and workflow efficiency. Dashboard color indicators were also found helpful in enabling real-time responses. Conclusion: The implementation of a boarding time monitoring dashboard significantly enhanced the ED's ability to reduce patient retention times. Results support the broader adoption of digital monitoring systems to improve patient flow and satisfaction.